Population genomics reveals distinct lineage of the Asian soybean rust fungus Phakopsora pachyrhizi in the United States of America unrelated to Brazilian populations - Ferreira, E.G.C.; Inoue, Y.; Murithi, H.; Nardwattanawong, T.; Cheema, J.; Grootens, R.; Paes, S.A.; Mahuku, G.; Joosten, M.H.; Hartman, G.; Yamaoka, Y.; Aime, M.C.; et al. (2025)
Asian soybean rust (ASR), caused by the obligate biotrophic fungus Phakopsora pachyrhizi, was first reported in the continental United States of America (USA) in 2004 and over the years has been of concern to soybean production in the United States. The prevailing hypothesis is that P. pachyrhizi spores were introduced into the United States via hurricanes originating from South America, particularly hurricane Ivan. To investigate the genetic diversity and global population structure of P. pachyrhizi, we employed exome-capture based sequencing on 84 field isolates collected from different geographic regions worldwide. We compared the gene-encoding regions from all these field isolates and found that four major mitochondrial haplotypes are prevalent worldwide. Here, we provide genetic evidence supporting multiple incursions that have led to the currently established P. pachyrhizi population of the United States. Phylogenetic analysis of mitochondrial genes further supports this hypothesis. We observed limited genetic diversity in P. pachyrhizi populations across different geographic regions, suggesting a clonal population structure. Additionally, this study is the first to report the F129L mutation in the Cytb gene outside South America, which is associated with strobilurin tolerance. This study provides the first comprehensive characterisation of P. pachyrhizi population structures defined by genetic evidence from populations across major soybean-growing regions.